2012
DOI: 10.1056/nejmsa1114353
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Health Disparities among Fifth-Graders in Three Cities

Abstract: We found that harmful health behaviors, experiences, and outcomes were more common among black children and Latino children than among white children. Adjustment for socioeconomic status and the child's school substantially reduced most of these differences. Interventions that address potentially detrimental consequences of low socioeconomic status and adverse school environments may help reduce racial and ethnic differences in child health. (Funded by the Centers for Disease Control and Prevention.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
157
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 145 publications
(165 citation statements)
references
References 46 publications
8
157
0
Order By: Relevance
“…We used data from Healthy Passages ™ , a multisite community cohort study of adolescent at NTNU -Trondheim on December 5, 2014 hpq.sagepub.com Downloaded from health and health behaviors initiated in 2004 (Schuster et al, 2012;Windle et al, 2004). Data were collected from the same cohort of youth while in fifth grade and then 2 years later when they generally were in seventh grade.…”
Section: Methodsmentioning
confidence: 99%
“…We used data from Healthy Passages ™ , a multisite community cohort study of adolescent at NTNU -Trondheim on December 5, 2014 hpq.sagepub.com Downloaded from health and health behaviors initiated in 2004 (Schuster et al, 2012;Windle et al, 2004). Data were collected from the same cohort of youth while in fifth grade and then 2 years later when they generally were in seventh grade.…”
Section: Methodsmentioning
confidence: 99%
“…We used data from Healthy Passages, a multisite, longitudinal community cohort study of adolescent health and health behaviors and their correlates (Schuster et al, 2012;Windle et al, 2004). Wave I data were collected from the cohort in fifth grade and Wave II data 2 years later when most were in seventh grade.…”
Section: Methodsmentioning
confidence: 99%
“…30 Prior multivariate analyses of these data demonstrated that Black youth were more likely to have perpetrated both physical aggression (e.g., hit another child) and nonphysical aggression (e.g., put down another child to their face) than were White youth; although Latino youth were more likely to have perpetrated aggression than were White youth in bivariate analyses, this disparity was reversed in multivariate analyses. 31 Perceived discrimination was associated with mental health problems for both Black and Latino youth. 32 …”
Section: Introductionmentioning
confidence: 99%